Relacja Kościoła do Pisma Świętego według Johna Webstera = The Church’s Relation to the Holy Scriptures according to John Webster - Zatwardnicki, Sławomir (Verbum vitae, 2023)
The problem discussed in the article is the question of the relation of the Church to the Holy Scriptures in the works of John Webster. The first part presents the views of an Anglican theologian showing the ontology of the Scriptures in relation to ecclesiology. The second part critically evaluates them from the perspective of Catholic theology; for this purpose, in particular, Joseph Ratzinger’s theology was used. Webster presents the Church as a creatura verbi divini, whose constant feature is to be a listener of viva vox Dei. Therefore, he proposes to classify the Church in the category of "spiritual visibility." The concept of the Church he adopted involves the authority of the Holy Scriptures as an instrument for the Risen Christ to express the present word through the inspired words of the "prophets and apostles". The same Holy Spirit who enlightened the biblical authors and inspired them, also played a prime role in the formation of the canon. In Webster’s opinion, recognition of canonicity was, above all, an act of reception and an obedient acceptance of God’s gift. Many valuable insights of the scholar can be assimilated into Catholic theology, but only on the condition of a "counter-reformation" reading of the views of a thinker whose reflections are strongly marked by Reform theology. Possible use of Webster’s thoughts would involve broadening the understanding of the word of God, appreciating the mystery of the Ecclesia, and placing a stronger emphasis on the past dimension of biblical texts.